ENGLISH LANGUAGE EDUCATION STUDENTS’ ATTITUDE TO ENGLISH LANGUAGE LEARNING AT UNIVERSITAS NEGERI MAKASSAR - Permatasari, Hartika; Korompot, Chairil Anwar; Fauzan, Muhammad Miftah (Universitas Negeri Makassar, 2026)
The purpose of this study is to determine the attitudes of English education students at Makassar State University's English Department toward English language learning during the fourth semester of the 2023–2024 academic year. Because the descriptive quantitative approach can be utilized to get information on students' perceptions of linguistic attitudes, the researcher used it as the design method. A questionnaire was also provided to gather data. Thirty students from classes A, B, and D at Universitas Negeri Makassar made up the study's sample. The sample was gathered using the Random Sampling Technique. With 15 (50%) students classed as having a good attitude and 15 (50%) as having a neutral attitude, the results demonstrated that students generally had a fairly positive and neutral attitude. Since they understand the many advantages of learning the language, pupils' motivation in English is inextricably related to their optimistic outlook. 72% of students strongly felt that it is very important for their academic and future professional lives, according to these statistics.